LIVING STANDARDS IN MODERN GERMANY - L. D. Efanova; S. A. Shmukler (Вестник университета)
This article reflects the main directions of achieving an optimal standard of living for German citizens, determines the main aspects of its maintenance. It has been noted, that the citizens of Germany have a sufficiently high, in comparison with other countries, standard of living, all the necessary social guarantees for decent living. Today, Germany is the optimal country for living, which forms a socially-oriented economy. The most priority feature of the implemented policy of the country is, that all the rights of citizens are realized in practice, and criminality is almost not widespread.